Hatékony eszköz-e az emberi értelem a fajunk hosszútávú túléléséhet? - Bálint, Botond (Kultúratudományi Szemle, 2024)
Is human intelligence a powerful tool for the long-term survival of our species? At the moment, it does not seem to be. In recent decades, with incredible ingenuity, humans have found a way to use everything around us as a resource, creating an endless illusion of abundance. The experience of immediate human memory is contrary to the evolutionary experience that there is no such thing as infinite abundance; it is always just a preparation for scarcity. At the level of humanity, we have no reflection on this otherwise recognised problem. We must ask ourselves, is our intelligence relevant to the totality of the biosphere, and are we capable of 'acting intelligently' as a group and as a whole species, can our response be planetary in scale? So far, we have used our intelligence locally very effectively there; we have been able to act rationally at that level, but not in the context of the whole biosphere as a species.